More on the question 'When does absence of evidence constitute evidence of absence?' How Bayesian confirmation theory can logically support the answer. (August 2019) - Taroni, F.; Bozza, S.; Hicks, T.; Garbolino, P.
Abstract: In forensic science it is not rare that common sayings are used to support particular inferences. A typical example is the adage 'The absence of evidence is not evidence of absence'. This paper analyzes the rationale hidden behind such statement and it offers a structural way to approach the analysis of this particular adage throughout a careful analysis of four different scenarios.